Morbidity pattern and health-seeking behaviour among the senior citizens in selected rural areas of Bangladesh (Journal of Dhaka Medical College, 2015)
Background: The purpose of this study was to determine the morbidity pattern and health seeking behaviour among the rural elderly population. Methods: This cross sectional study was conducted in six villages of Telihati union of Gazipur District from February to June 2013. Purposive sampling technique was used to collected data from 249 respondents, aged 60 years and above. Results: The mean age of the respondents was 64.2 (SD±5.6) years. About 70.3% of the respondents were male, majority (47%) respondents were illiterate, 33.3% earned less then ten thousand taka per month. About half (58.2%) of the elderly were still working, among the currently not working respondents majority (49%) were totally dependent. and only 52.6% respondents belonged to joint family. Almost all (98.8%) the respondents had some health problems; among these eye problems (81.7%), musculo-skeletal disorders (66.3%), gastrointestinal disorders (52.4%) and sleeping problems (50.4%) were predominant. Females suffered more from eye problems, musculoskeletal disorder, gastrointestinal disorder and sleeping problems. On the other hand, males suffered more from respiratory and genitorurinary problems. About 61% have a Government hospital or Community clinic nearby their residence, 70 % were satisfied with available health care facilities and 72% was satisfied with treating doctors even then a greater part (35%) was irregular for check-up. Majority (73.5%) was regular about taking treatment, among the irregulars majority (77.3%) was for un-affordability of medicine. Only 53% of the elderly knew names of some old age diseases. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21522 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 129-135